Development of ego stages and intercultural sensitivity through doctoral study - Abigail Lynam; Steven Schapiro (Adult Education Research Conference, 2021)
This study explores the developmental diversity of incoming and graduating students regarding ego stage and intercultural sensitivity and how students develop in the context of their doctoral studies. It also examines the relationship and correlations between the two domains and how they each develop. In this paper, we report on the results in process in year two of this multi-year longitudinal study.
Keywords: Ego development; intercultural sensitivity; doctoral study; adult development